2020
DOI: 10.1096/fj.201902690r
|View full text |Cite
|
Sign up to set email alerts
|

Serine is required for the maintenance of redox balance and proliferation in the intestine under oxidative stress

Abstract: Serine has critical roles in maintaining cell growth and redox balance in cancer cells. However, the role of exogenous serine played in oxidative response and proliferation in normal mammalian intestine need to be further elucidated. We used a mouse model and intestinal porcine epithelial cells (IPEC‐J2) to reveal that exogenous serine deficiency did not lead to redox imbalance and inhibition of proliferation in the intestine. However, serine deficiency exacerbated oxidative stress, mitochondrial dysfunction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…The metabolism of serine involves one-carbon metabolism. The role of serine on cancer cell and T-cell proliferation is well recognized to provide substrates for the synthesis of nucleotides, NADPH, and glutathione ( 41 , 42 ). It was recently shown that serine supports lipopolysaccharide-induced IL-1β production in macrophages ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of serine involves one-carbon metabolism. The role of serine on cancer cell and T-cell proliferation is well recognized to provide substrates for the synthesis of nucleotides, NADPH, and glutathione ( 41 , 42 ). It was recently shown that serine supports lipopolysaccharide-induced IL-1β production in macrophages ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serine is a nutritionally nonessential amino acid, but it is a major substrate for the synthesis of glutathione. Recent studies demonstrated that dietary supplementation with serine showed strong anti-inflammatory and antioxidative abilities in certain mouse models [7][8][9][10]. Moreover, serine exerted beneficial effects on microbiota composition and alleviated inflammatory responses in a dextran sulfate sodium-induced colitis model in mice [11].…”
Section: Introductionmentioning
confidence: 99%
“…Little attention has been paid to the influence of dietary Ser supplementation or its deficiency on serum biochemistry or features of the immune system of laying hens, although its anti-inflammatory and anticancer effects are well documented in vitro or in vivo ( Stiuso et al., 2016 ; Newman and Maddocks, 2017 ; He et al., 2020 ). Serum biochemical indices can partly reflect the metabolism and health status of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…As the major carbon donors of one-carbon metabolism, Ser helps coordinate synthesis of nucleotide, S-adenosyl-methionine, NADPH, and glutathione ( Yang and Vousden, 2016 ). It has been confirmed that dietary Ser supplementation can prevent against oxidative stress because of its role in glutathione synthesis ( Zhou et al., 2017 ; He et al., 2020 ). Ma et al.…”
Section: Introductionmentioning
confidence: 99%